2008
DOI: 10.1007/s11548-008-0253-2
|View full text |Cite
|
Sign up to set email alerts
|

Robotic alignment of femoral cutting mask during total knee arthroplasty

Abstract: Objective To investigate a new navigation system integrated with a robotic arm for total knee replacement (TKR) procedures. Materials and MethodsThe study here reported attempts providing the surgeon with a robotic assistant handling the surgical tools with superior stability removing tremors. The system is equipped with an optical localization system, which allows the real-time monitoring of the position and orientation of the surgical tools carried by the robot end-effector and provides a feedback control to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…Calibration inaccuracies can be due to noise in the measurement system or to robot inaccuracies. Previous work [17,18] showed that hand-eye calibration errors are in the range of 0.06 mm for translation values and 0.03 rad for rotation values, which are two orders of magnitude less than the N MAX � we computed. Independent of calibration, the targeting accuracy has to be less than 1 mm at the target point.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Calibration inaccuracies can be due to noise in the measurement system or to robot inaccuracies. Previous work [17,18] showed that hand-eye calibration errors are in the range of 0.06 mm for translation values and 0.03 rad for rotation values, which are two orders of magnitude less than the N MAX � we computed. Independent of calibration, the targeting accuracy has to be less than 1 mm at the target point.…”
Section: Discussioncontrasting
confidence: 55%
“…They can also be used to register the intraoperative reality on the preoperative images [29], thus allowing the surgical tool's navigation and enabling compensation for patient motion in several medical applications. Such deviations happen because serial robots have low absolute accuracy due to the fact that robots' models are inaccurate [21, 22], but also because the calibration between the robot's space and the measurement system is affected by errors [18]. Moreover, external sensors in the operating room can be used to detect and compensate for possible motion during the intervention [23] or during trans-cranial magnetic stimulation in order to maintain the stimulating probe on the planned pose [24, 25].…”
Section: Introductionmentioning
confidence: 99%
“…In order to compute the spatial transformations between the robot internal sensors (encoders) and the optical tracking system, the approach described in [17] was used to calibrate both the GP and the FP. X GP , Y GP , X FP and Y FP represent the transformations between the DRFs in the optical reference frame and the robots internal reference frame (see Fig.…”
Section: B Spatial Relationsmentioning
confidence: 99%
“…The registration/calibration, e.g. between the optical and electromagnetic reference systems, was performed using algorithms developed in , whereas patient registration to preoperative image space was accomplished using the Horn method . IGSTK is mainly used for spatial relationship hierarchy definition among reference frames and for tracking data acquisition.…”
Section: Methodsmentioning
confidence: 99%
“…Using a software‐based application for time‐stamping external information induces a temporal imprecision, which can be due to the offset of the PC clock with respect to a reference time and to the drift of the internal clock (frequency error) . Spatial consistency is also required when dealing with different sensors information; spatial transformations between reference systems are obtained with calibration procedures .…”
Section: Introductionmentioning
confidence: 99%